Cervical human papillomavirus prevalence, risk factors and outcomes in a cohort of HIV-infected women in Harare, Zimbabwe - Ardele M. Mandiriri; Margaret J. Pascoe; Tinei Shamu; Sara Lowe (AOSIS, 2020)
Background: Human papillomavirus (HPV) associated invasive cervical cancer (ICC) is common in Zimbabwe, disproportionately affecting women living with HIV (WLHIV). Understanding high-risk HPV (hrHPV) infection in relation to cervical disease is important for ICC prevention amongst WLHIV. Objectives: To describe the prevalence of cervical hrHPV, type distribution, associated risk factors and ICC screening outcomes in an urban cohort of Zimbabwean women. Methods: In this cohort study, WLHIV were tested for hrHPV infection using the Cepheid Xpert® HPV assay and followed up for incident cervical disease. Follow-up assessments were done by visual inspection with acetic acid (VIA). Descriptive statistics and logistic regression were used to describe hrHPV burden and association between hrHPV and potential risk factors. Incidence rates (IR) and rate ratios of cervical disease by hrHPV infection status were also calculated. Results: Amongst 321 WLHIV recruited, hrHPV prevalence was 24.9% (n = 80). Fifty-two of these women (65%) were positive for hrHPV types other than 16 or 18/45. Younger age (22-29 years), early sexual debut (13-16 years) and antiretroviral therapy (ART) regimen (second-line ART) were independently associated with hrHPV positivity. Positive VIA IR ratio between hrHPV-positive and -negative women was 12.57 (95% confidence interval [CI]: 4.14-38.19). Only women with hrHPV infection had incident cervical disease (IR: 6.41/100 person-years, (95% CI: 3.33-12.32). There were no ICC cases by the end of the 2-year follow-up. Conclusion: There was a high prevalence of hrHPV infection other than 16 and 18/45 in this cohort. Integrating HPV testing in cervical cancer screening programmes may increase screening intervals in hrHPV-negative women, reducing costs for programmes. We recommend further research into cross protectivity of the bivalent and quadrivalent HPV vaccines against these other hrHPV types.